CHEMOSYSTEMATICS AND INDIGENOUS USES OF SHOREA IN SOUTH ASIA - KUNJANI JOSHI (International Journal of Pharma and Bio Sciences, 2011)
The Genus Shorea Roxb. ex Gaertn. (Dipterocarpaceae) is rich in species diversity with 194 species. In South Asia, the species of Shorea show great variation in morphological characters. These species are dominantly distributed in the forest habitats of the tropical and some parts of subtropical zones. Since more than two decades, the taxonomy of Shorea has been a point of discussion. Time to time, various taxonomists have tried to classify the species of Shorea on the basis of anatomical and morphological characters. This type of controvercy in the arrangement of the species can also be solved by the study of chemicals. Information regarding chemical constituents of the species of Shorea is very limited. Among the chemical constituents present in different parts of the plants, flavonoids are already proved as potentially important markers for taxonomic studies due to its characteristics such as structure variability, chemical stability, ubiquitous occurrence and easy and rapid identification. During the chemotaxonomic study of Shorea of South Asia, flavonoid aglycones (flavonol quercetin, myricetin, kaempferol, and flavones luteolin, apigenin and proanthocyanidin) and four flavonoid glycosides (quercetin 3-glucoside, quercetin 3-rutinoside, kaempferol 3,5-glucoside, and luteolin 7- glucoside) were isolated from the leaves of Shorea using standard procedures after separation and purification by paper chromatography in several solvent systems. The isolated flavonoids can be used as chemotaxonomic markers and also as active ingredients of many medicines. The ethnobotanical study of the species of Shorea was also carried out. At present, the species of Shorea and their parts are under serious threat due to habitat destruction and over-exploitation. An integrated approach is, therefore, essential for the sustainable management of Shorea. Strategies for sustainable management of the species have also recommended.